Marital Flourishing on The Husbands of Migrant Worker Who Maintain Their Marriage - Adelina, Femita; Hartini, Nurul; Suryanto, (International Journal of Psychosocial Rehabilitation, 2020)
Maintaining a marriage by a migrant worker husbands from Indonesia was an interesting phenomenon to be investigated. This was because of high divorce proposal on the spouse of women migrant worker; but on the other hand there were many migrant worker spouse who can survive their marriage. The purpose of this research was to examine the contribution of meaning, personal growth, goal sharing, relational giving, personal expressiveness, and engagement dimension in measuring marital flourishing of migrant worker husbands. The analysis technique used was confirmatory factor analysis on 50 subjects of survey research. The research results showed that those six dimensions contribute in measuring marital flourishing of migrant worker husbands with loading factor value was bigger than 0,90.